State of Women's Empowerment and Community Perception in Rural Pakistan (A Case Study of Malakand Division) - Naz, Arab; Khan, Waseem; Khattak, Mamoon Khan; Daraz, Umar; Mughal, Irum; Khan, Muhammad Asghar (Asian Journal of Empirical Research, 2013)
Development of a nation depends upon the active involvement of both male and female at the grassroots level. Women empowerment is crucial for community development and sustainable solutions to various problems at a large scale. The current study is an attempt to investigate community perception towards women’s empowerment in Malakand division, Khyber Pakhtunkhwa Province of Pakistan. Data is obtained from 225 respondents including youth, women, men and local elders (particularly leaders) in five (05) villages through structured interview schedule and the responses have been obtained on a Likert-type scale for analysis to show agreement or disagreement of the respondents. The study shows that women’s empowerment in terms of mobility, economic resources, decision-making, political participation, and awareness creation lacks parity and females are more deprived in this regard. The study suggests that women in particular need more education, capacity building, employment, control over resources and economic opportunities.